#TITLE_ALTERNATIVE# - NICODEMUS TARIGAN (NIM : 13206075) ;pembimbing : Ir. Hardi Nusantara, MT., ORYZA
The emergence of variety of telecommunications services in the world that demand large bandwidth has been carrying IP over WDM networking technology as the right answer in dealing with these conditions. WDM network design that requires certain specifications to ensure the performance of IP traffic is carried into the needs of network planning. This final project investigates the influence of components in the design of WDM networks for IP performance. Simple network design done for then studied further in the mathematical theory approach. WDM network design is done by considering the loss, dispersion, and nonlinear effects in theory. The feasibility of the network is then calculated by power budget method for a particular scenario. By this power budget method, the value of OSNR can be calculated. Furthermore, the addition of the components in the WDM network and see its effect on the value of OSNR. Based on these data OSNR values, it can be seen the relationship with a packet loss of WDM components in theory. To delay and throughput, a review is conducted in the theory of the network designed. Study results showed that the addition of components in the WDM network will cause a smaller OSNR values. The smaller OSNR makes the smaller Q-factor as well. Q-factor decrease in the value of making greater BER. The increament of the value of BER create higher levels of packet loss.